LOKAKARYA KOLABORATIF TENTANG INTEGRASI ANTARA SISTEM SUBAK, KREATIVITAS VISUAL DAN CHATGPT DI SMAN 1 MENGWI BADUNG BALI - Surata, Sang Putu Kaler; Arjaya, Ida Bagus Ari; Paraniti, Anak Agung Inten; Hermawan, I Made Surya (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Educators face the significant challenge of integrating modern technological advancement and local wisdom into sustainable life practices as digital technology rapidly evolves. To address this, a day-long collaborative workshop was executed, involving 44 SMAN 1 Mengwi Badung Bali teachers, 4 students, and 4 lecturers from the Department of Biology Education, Universitas Mahasaraswati Denpasar. By using the subak system, ChatGPT, and drawing exercises, the workshop aimed to improve knowledge, engagement, abilities, and motivation for innovative learning. Orientation, individual tasks, group conversations utilising ChatGPT, classroom presentations, and reflections were all part of the activities, which were evaluated by participant observation, interviews, and document analysis. The findings revealed active engagement throughout the activities, an improved understanding of the subak system's cultural and environmental values, proficiency in using ChatGPT, and a desire to apply creative skills for integrated learning. Furthermore, the workshop developed a collaborative community among educators, students, and lecturers, encouraging the exchange of insights, experiences, unique ideas, and inspirational learning methodologies.